2010
DOI: 10.1038/hdy.2010.155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human perturbation on the genetic make-up of an island population: the case of the Sardinian wild boar

Abstract: Game species are often manipulated by human beings, whose activities can deeply affect their genetic make-up and population structure. We focused on a geographically isolated wild boar population (Sardinia, Italy), which is classified, together with the Corsican population, as a separate subspecies (Sus scrofa meridionalis). Two hundred and ten wild boars collected across Sardinia were analysed with a set of 10 microsatellites and compared with 296 reference genotypes from continental wild populations and to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 34 publications
5
48
1
3
Order By: Relevance
“…No official records exist about wild pig translocations into these particular sites, but the genetic uniqueness compared to wild pigs from other surrounding locations suggests that animals at these sites were recently introduced. This introduction would likely be associated with unreported/illegal transport and release to increase local hunting opportunities (Vernesi et al 2003;Spencer and Hampton 2005;Scandura et al 2011;Lopez et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No official records exist about wild pig translocations into these particular sites, but the genetic uniqueness compared to wild pigs from other surrounding locations suggests that animals at these sites were recently introduced. This introduction would likely be associated with unreported/illegal transport and release to increase local hunting opportunities (Vernesi et al 2003;Spencer and Hampton 2005;Scandura et al 2011;Lopez et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous population genetic studies of wild pigs, largely conducted in Europe and Oceania, have identified individual membership to particular populations and levels of population admixture (i.e. interbreeding among isolated populations which produces offspring with a mixture of alleles from different ancestral populations) (Vernesi et al 2003;Hampton et al 2004;Spencer and Hampton 2005;Nikolov et al 2009;Scandura et al 2011;Lopez et al 2014). Although these data will help inform population management and control efforts, little is known about wild pig dispersal and expansion throughout North America.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, mtDNA sequencing, microsatellite genotyping, and a single-nucleotide polymorphism (SNP) assay have been used to look for evidence of introgression (Giuffra et al 2000;Scandura et al 2008, 2011b, Frantz et al 2012, 2013, Goedbloed et al 2013bHerreroMedrano et al 2013;Iacolina et al 2016b).…”
Section: Introductionmentioning
confidence: 99%
“…Scandura et al 2011a;Frantz et al 2012Frantz et al , 2013. Microsatellite loci are very useful to analyze gene flow and admixture even between closely related populations due to their high level of polymorphism and mutation rate (Roy et al 1994) and they have been widely used in combination with Bayesian clustering and admixture analysis (Pritchard et al 2000) in order to analyze hybridisation between wild boars and different pig breeds (e.g.…”
mentioning
confidence: 99%